The prospect of oil palm trunk for manufacturing laminated veneer lumber (LVL) / Ahmad Fauzi Puasa and Hashim W Samsi - Puasa, Ahmad Fauzi; W Samsi, Hashim (Universiti Teknologi MARA Cawangan Pahang, 2008)
Since 1995, Malaysia has faced a shortage of supply of logs for local wood based industry in order to maintain existing production level in the country. The increase in prices for logs has worsened the wood-based industry especially the furniture industry. Continuous campaigns by environmentalists against the use of tropical hardwood have also influenced our hardwood production. As such, the introduction and utilisation of oil palm biomass as an alternative source of raw material, is indeed timely for our wood-based industry. Oil palm trunk (OPT), a biomass by-product used in this project, is an agricultural waste of oil palm plantation. Technically, it is considered as 'environmentally friendly' or 'green' material, renewable resources, harvested and managed under sustainable plantation by established and certified corporations. OPT-based products are considered new and at the infancy stage of development. Research has been carried out for the pass few years on the lab scale basis. Being pioneers in oil palm, the source of matured OPT are abundant in Malaysia. A series of R&D that has been carried out by FRIM indicates that OPV has tremendous commercial potential as core-materials for industrial application especially the LVL. With the LVL, many other panel-products can be produced such as furniture and components, panelling, door and flooring core content, wall frames and partitions, door frames, building components and etc. However, none of these studies worked on the commercial applications, i.e. machinery and economic scale. Using this technical know how, this paper studies the viability of the establishment of the LVL plan on the commercial scale in Malaysia with the Malaysian experience. However, the existing machinery, equipment and production set up for making plywood could be further modified Jurnal Gading for making the LVL using OPT. Furthermore, anatomically OPT is not truly a woody material; it requires a special type of machine to enable OPT for the LVI. Most of the woodworking machinery manufacturers are mainly from overseas such as USA, Germany, Italy, Japan, Taiwan and Chin., They may not know much about the characteristics of oil palm trunks. Findings from this paper should be able to support the supply of raw materials for the wood-based industry.